The Practice of Buying and Selling Online Using the Cash On Delivery Method on the Shopee Application in the Perspective of Islamic Law: A Case Study of Students of the Az-Zaytun Islamic Institute of Indonesia - Intan Khoiriyah; Rizal Maulana (JOURNAL of LEGAL RESEARCH, 2022)
The mechanism of buying and selling carried out online has advantages for Shopee application users who do not have an e-wallet and can minimize the occurrence of fraud. However, Cash on Delivery payment transactions on the Shopee application lately often cause problems made by buyers because buyers are not responsible for making payments that result in cancellations in their transactions. The factors behind the cancellation of the contract in the Cash on Delivery transaction on the Shopee application are that the goods do not match the product description, the buyer does not have money to pay, the goods are damaged when received, the buyer cannot be contacted, and the buyer changes his mind to buy. The practice of buying and selling using the Cash on Delivery method on the Shopee application is in accordance with Islamic law. Where buying and selling in Islam is given the freedom to choose to cancel the trade contract or continue the trade contract.